2005
DOI: 10.4103/0019-5359.18965
|View full text |Cite
|
Sign up to set email alerts
|

Accurate blood pressure recording: Is it difficult?

Abstract: BACKGROUND: Blood pressure (BP) measurement is a routine procedure but errors are frequently committed during BP recording. AIMS AND SETTINGS: The aim of the study was to look at the prevalent practices in the institute regarding BP recording. The study was conducted in the Medicine Department at Government Medical College, Chandigarh, a teaching institute for MBBS students. METHODS: A prospective, observational study was performed amongst the 80 doctors in a tertiary care hospital. All of them were observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…However, many publications have pointed out the lack of formal training and assessment in BP measurement during undergraduate and postgraduate medical training, and this could have been responsible for our findings 9,19,24-26. In fact, Gonzalez-Lopez et al 24 pointed out that inadequate knowledge of BP measurement is unlikely to improve during specialised postgraduate training since the skill is not taught during this period because of the assumption that the relevant skill should have been acquired earlier on during undergraduate training.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, many publications have pointed out the lack of formal training and assessment in BP measurement during undergraduate and postgraduate medical training, and this could have been responsible for our findings 9,19,24-26. In fact, Gonzalez-Lopez et al 24 pointed out that inadequate knowledge of BP measurement is unlikely to improve during specialised postgraduate training since the skill is not taught during this period because of the assumption that the relevant skill should have been acquired earlier on during undergraduate training.…”
Section: Discussionmentioning
confidence: 86%
“…Although protocols for measuring BP are well described and standardised,2-5 inaccuracies of measurement do occur from the use of faulty or malfunctioning equipment, improper technique, or observer errors or bias 5-9. Observer biases described in clinical practice and trials include duplication of previous BP recordings, rounding off to or below pre-set cut-off values for the diagnosis or control of hypertension and rounding off BP values to a particular end digit 5-20…”
Section: Introductionmentioning
confidence: 99%
“…Half of the GPs from this study were not allowing the rest period, which is comparable with an Indian study that showed that 70% of the consultants and residents did not let patients rest before measurement. 18…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio observacional en la Westminster School de Londres, el 33% de 80 médicos internos residentes declaró no habérsele enseñado la toma de la TA; posteriormente, se comprobó que la tomaban de forma incorrecta [8]. De interés en el estudio mencionado, no se hallaron diferencias debidas a lateralización, mientras que sí se detectan en el nuestro.…”
Section: Discussionunclassified